Perencanaan Ulang Gedung Rumah Sakit AN-NUR Yogyakarta Dengan Beton Bertulang - Irfan, Andy Rosyulianta; , Ir. Abdul Rochman, M.T; , Mochamad Solikin, S.T, M.T, Ph.D (2015)
Yogyakarta rapidly growing in terms of both business and infrastructure makes the needs for hospital increased. Therefore it will be planned a 3 floors apartment building with 1 basement in Yogyakarta using High bearer Moment Frame System (SRPMM). The structure of the building which planned must be consider safety aspects, architectural and economic. The plane of apartment building refers to the regulatory standards (SNI) version that has been published, that is SNI-1726: 2012 (Procedures Planning of Earthquake Resistance For Building Structure and Non-Building) and SNI-2847: 2013 (Concrete Structural Requirements To Building). The plan of this building including the main structure (the columns and beams structure) and the roof truss steel structure and plate structure (floor plate, basement walls and stairs). Classification calculation of land sites including SD category (medium soil), then the values of SDS and SD1 are 1.226 and 0.448 so the classification counted as Seismic Design Category (KDS) for this planning counted as KDS D (risk major earthquake). For the planning requirements of loads earthquake on SRPMK building, using virtue factor Ie building with value of 1.0 (residential, risk category II) modification factor response (R) with value of 5, deflection magnification factor (Cd) with value of 2.5. f'c '25 Mpa used for concrete quality, and steel reinforcement using 400 Mpa BJTs and 240 MPa BJTP. The 350/700 beam dimension used for the 1st and 2nd floor, the 300/600 beam dimension used for the 3rd until 4th floor. For the basement until 2nd floor, 450/600 can be used as column dimensions and 3rd until 4th floor can be used 300/500 for column dimension. The ground structure expected using soles wear foundation with 1 m depth. Key words : building structure, medium bear moment frame, system planning.